Are smart refrigerators the way of the future for storing food? - V. Basil Hans (International Journal of Advanced Control and System Engineering, 2026)
Smart refrigerators are changing the way people store food by using new technologies including Wi-Fi, artificial intelligence (AI), internal cameras, voice control, and inventory management systems. This article looks at how smart refrigerators are changing in homes and businesses, looking at how they could make things easier, cut down on food waste, and save energy. New technologies including Wi-Fi, internal cameras, voice control, artificial intelligence (AI), and inventory management systems are transforming how consumers keep food in smart refrigerators. In order to reduce food waste, save energy, and make life easier, this article examines how smart refrigerators are evolving in households and workplaces. The study examines the current market, user benefits, and technology issues to determine whether smart refrigerators are a practical innovation or only a fad. Concerns like cost, long-term reliability, and data privacy are also covered. The essay looks at the existing market, the benefits to users, and the technological problems to see if smart refrigerators are a useful new idea or just a luxury trend. It also talks about worries about data privacy, cost, and long-term dependability. Ultimately, the article wants to find out if smart refrigeration is a big change in how food is stored or just a small change in how appliances are made.
Keywords: AI (Artificial Intelligence); Food Storage; Internet of things (IoT); Smart appliances; and home automation; energy efficiency; refrigeration technology